TBL Through Music to Foster Students’ Lexical Competence - Ladino Herrera, Luisa Fernanda; Pérez Molina, Geraldyne; Hernández Prieto, Heiryn Dayanne; Gomez Villalba, Paula Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The topic of this qualitative action research was to evidence how Task Based Learning (TBL) through music could foster students’ lexical competence in a multi grade school based on “Escuela Nueva”. The population of the research was a primary school of a public institution that had difficulties in their lexical competence. The goal of this research was to explore the impact that Task Based Learning through music had on students’ lexical competence in an environment of “Escuela Nueva”. The instruments to gather the data were field notes, videotape recordings, pictures, and questionnaires. Findings of this study evidenced that this type of musical tasks can foster lexical competence and engage students to participate actively in class. Likewise, results showed that students were able to relate and recognize words, thanks to the implementation of musical activities as well as the fact that practicing vocabulary with songs can become a good strategy to develop students’ higher level of comprehension.